Analysis of variable magnetic field on chemically dissipative MHD boundary layer flow of Casson fluid over a nonlinearly stretching sheet with slip conditions. Issue 1 (31st December 2022) - Senapati, Madhusudan; Parida, Sampad Kumar; Swain, Kharabela; Ibrahim, S. Mohammed
ABSTRACT: Casson fluid model is a non-Newtonian fluid with yield stress which is widely used for modelling blood flow in narrow arteries. The present study investigates the slip flow analysis on magnetohydrodynamic flow of a Casson fluid over a nonlinearly permeable stretching sheet embedded in a porous medium. The heat transfer equation is modelled with the influences of thermal radiation, viscous dissipation, Joule heating and uniform heat source. Further, the chemically reactive species enriches the study of chemical reaction. Using similarity transformations the governing equations are converted into ordinary differential equations which are solved numerically using shooting technique. The influences of various pertinent parameters are explained through graphs and tables. It is found that suction and injection have opposite effects on velocity profiles. Further, Eckert number enhances the rate of heat transfer but reduces the mass transfer at the bounding surface.